FINANCIAL DECISION MODEL FOR THE PROPERTY-LIABILITY INSURER: AN ALTERNATIVE TO THE NAIC MODEL INVESTMENT LAW - Bachman, James E.; Lamm-Tennant, Joan (Assurances)

(untitled) (HEC Montréal, 1997)
In an attempt to curb the inappropiate investment practices of the past, the National Association of Insurance Commissioners (NAIC) have proposed the Model Investment Law. Although the most recent draft of the Model Investment Law is less complex and offers increased flexibility in certain investment areas, it continues to receive criticism since it uses a "pigeon hole" approach with asset limitations based on definitional classifications that apply to all companies. This paper proposes a methodology for establishing a strategic asset allocation for the property-liability insurer while recognizing the confounding influences of capital structure and product line mix. The methodology is developed in accordance with mean-variance efficiency on an after-tax basis.